EuroGuiDerm Guideline on the systemic treatment of Psoriasis vulgaris – Part 1: treatment and monitoring recommendations. (21st December 2020) - Nast, A.; Smith, C.; Spuls, P.I.; Avila Valle, G.; Bata‐Csörgö, Z.; Boonen, H.; De Jong, E.; Garcia‐Doval, I.; Gisondi, P.; Kaur‐Knudsen, D.; Mahil, S.; Mälkönen, T.; et al.
Abstract: This evidence‐ and consensus‐based guideline on the treatment of psoriasis vulgaris was developed following the EuroGuiDerm Guideline and Consensus Statement Development Manual. The first part of the guideline includes general information on the scope and purpose, health questions covered, target users and strength/limitations of the guideline. Suggestions for disease severity grading and treatment goals are provided. It presents the general treatment recommendations as well as detailed management and monitoring recommendations for the individual drugs. The treatment options discussed in this guideline are as follows: acitretin, ciclosporin, fumarates, methotrexate, adalimumab, apremilast, brodalumab, certolizumab pegol, etanercept, guselkumab, infliximab, ixekizumab, risankizumab, secukinumab, tildrakizumab and ustekinumab.